New Avenues in Radical Trifluoromethylselenylation with Trifluoromethyl Tolueneselenosulfonate - Ghiazza, Clément; Monnereau, Cyrille; Khrouz, Lhoussain; Médebielle, Maurice; Billard, Thierry; Tlili, Anis (Synlett, 2019)
We demonstrated that the shelf-stable reagent trifluoromethyl tolueneselenosulfonate can be involved in radical trifluoromethylselenylation. Upon visible-light irradiation, the homolysis of the reagent could take place at room temperature. This finding is explored for unprecedented C(sp2)–SeCF3 and C(sp3)–SeCF3 processes under transition-metal-free conditions. Mechanistic investigations, including cyclic voltammetry, luminescence measurement, and EPR studies, allowed the proposal of plausible mechanisms.1 Introduction.2 Reactivity of Reagent I with Diazonium Salts3 Reactivity of Reagent I with Alkenes and Alkynes4 Conclusion
Keywords: trifluoromethylselenylation; trifluoromethyl tolueneselenosulfonate; arenediazonium salts; eosin Y; photochemistry; radical reactions